Penguatan Legalitas Usaha Melalui Pembuatan Nomor Induk Berusaha di Sentra Wisata Kuliner Penjaringansari - Aisyah Hanif; Ika Korika Swasti (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Business legality is the main thing that business people need to do when starting a business. With business legality, the business being run can be said to be feasible to operate where legality is a license to run a business given by the authorities. Penjaringansari Culinary Tourism Center is one of the gathering places for business actors engaged in the culinary field who are experiencing problems related to the lack of awareness of the importance of legality in a business. This activity was carried out at the Penjaringansari Culinary Tourism Center which aims to provide education related to making a Business Identification Number and providing assistance in making a Business Identification Number. The method of implementing this activity is divided into three stages, including: the observation and interview stage, the stage of providing education, and the implementation stage. The target of this activity is business actors who do not yet have a Business Identification Number at the Penjaringansari Culinary Tourism Center, namely 13 business actors. The result of this activity is that the desire and awareness in developing the business being run is increasing because it already has a business license that is protected by applicable law.